산업용 디젤엔진에 대한 코로나탈질기술 적용에 관한 연구 - 장홍기(Hong Ki Chang); 최창식(Chang Sik Choi); 신중욱(Jung Uk Shin); 지영연(Young Yeon Ji); 홍민선(Min Sun Hong); 정윤진(Yoon Jin Chung) (Daehan hwan'gyeong gonghag hoeji, 2007)
We have studied to find out the possibilities and economical efficiencies of multi-staged corona DeNOx process which is applicable for the industrial power facilities. Especially, We focused on the relation between DeNOx efficiencies and energy costs, and the test result showed that the energy costs seem to be lowered at high flow rates and low NOx concentrations. 7.5 kW pulsed power supply test showed that the 15 kW pulse power supply might be required for the 0.6 MW industrial diesel engine exhaust gas treatment with 65% DeNOx efficiency, and that the minimum $1.5{\sim}1.7 ms/ppm$ of residence time for optimal reactor design. Also, impedance matching between the energy cost and NOx removal efficiency is very important scale up factor to optimal reactor design and manufacturing for system stability. generally, about 30%(reactor capacitance versus pulse power supply capacitance) is optimal level and $20{\sim}25 J/pulse$ is optimal discharging energy. 다양한 배출 특성을 지닌 질소산화물을 제어하기 위해, 코로나 방전 탈질 시스템을 대용량 발전 설비에 적용해 그 가능성과 경제성을 파악하는 연구를 수행하였다. 특히, 탈질 효율과 소비에너지와의 상관관계를 파악하는데 중점을 두었으며, 실험한 결과 조건마다 약간의 차이는 있으나 유량이 많고 초기 농도가 낮을수록 소비에너지가 작아지는 경향을 확인할 수 있었다. 7.5kW급 출력용량의 펄스전원을 이용한 시험에선, 0.6MW급 발전시설의 배가스 처리를 위해 대략 15 kW급 출력용량의 펄스전원이 필요하다는 것을 알았다. 이 때 약 65% 정도의 탈질 효율을 나타냈으며 최적의 반응기 형태를 위해 $1.5{\sim}1.7ms/ppm$ 이상의 체류시간이 필요함을 알았다. 또한, 최적 반응기 설계 제작을 위한 임피던스 정합이 중요하며, 반응기 정전용량 대비 펄스전원 출력부의 30% 이내로 설계해 주었을 때 시스템이 안정적으로 운전됨을 확인하였다. 이 조건에서 반응기에 투입되는 최적의 펄스당 방전 에너지는 약 $20{\sim}25 J/pulse$ 범위일 때 최적의 제거효과를 보였다.